The (Dis)Advantage of Certainty: The Importance of Certainty in Language. Issue 1 (March 2014) - Corley, Pamela C.; Wedeking, Justin
<x xml:space="preserve">Abstract</x> How can legal decision makers increase the likelihood of a favorable response from other legal and social actors? To answer this, we propose a novel theory based on the certainty expressed in language that is applicable to many different legal contexts. The theory is grounded in psychology and legal advocacy and suggests that expressing certainty enhances the persuasiveness of a message. We apply this theory to the principal–agent framework to examine the treatment of Supreme Court precedent by the Federal Courts of Appeal. We find that as the level of certainty in the Supreme Court's opinion increases, the lower courts are more likely to positively treat the Court's decision. We then discuss the implications of our findings for using certainty in a broader context.